A CASE REPORT OF ISLET CELL CARCINOID AND MALIGNANT RETROPERITIONEAL FIBROUS HISTIOCYTOMA - Han, Guiqing; Zhang, Shuangmin (Chinese Journal of Cancer Research, 2013)
A 56 years old female patient, presented with a mass in left upper quadrant of the abdomen for four months and was hospitalized in August 29, 1995 because of acute abdominal emergency with nausea and vomiting. The patient appeared acutely ill hut was full consciousness. The physical examination was negative except for a mass measuring with tenderness and resistance was palpated in the left upper quadrant of the abdomen.